2013
DOI: 10.7150/ijbs.5781
|View full text |Cite
|
Sign up to set email alerts
|

Corpse Management in Social Insects

Abstract: Undertaking behavior is an essential adaptation to social life that is critical for colony hygiene in enclosed nests. Social insects dispose of dead individuals in various fashions to prevent further contact between corpses and living members in a colony. Focusing on three groups of eusocial insects (bees, ants, and termites) in two phylogenetically distant orders (Hymenoptera and Isoptera), we review mechanisms of death recognition, convergent and divergent behavioral responses toward dead individuals, and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 81 publications
4
100
0
Order By: Relevance
“…Social segregation between age groups is thus reinforced, providing organisational immunity (Stroeymeyt, Casillas Perez, & Cremer, 2014). The results obtained in our H colonies are consistent with previous studies performed by Arathi et al (2000), and Sun & Zhou (2013). They found that workers performing diseaserisk tasks are usually highly specialised and have few interactions with other workers.…”
Section: Discussionsupporting
confidence: 92%
“…Social segregation between age groups is thus reinforced, providing organisational immunity (Stroeymeyt, Casillas Perez, & Cremer, 2014). The results obtained in our H colonies are consistent with previous studies performed by Arathi et al (2000), and Sun & Zhou (2013). They found that workers performing diseaserisk tasks are usually highly specialised and have few interactions with other workers.…”
Section: Discussionsupporting
confidence: 92%
“…Highly valuable individuals appear to be protected against disease via interaction heterogeneities, which result in their social isolation from 'high-risk' individuals (i.e. old workers that have a high chance of having encountered pathogens and perform high disease-risk tasks such as foraging [2 ], waste management [35,36], undertaking [37] and hygienic behaviour [21]). There is good evidence that the queen and young workers are protected from potentially harmful external agents.…”
Section: Interaction Patterns and Individual Probability Of Infectionmentioning
confidence: 99%
“…Self-medication is widespread in animals (de Roode et al 2013), but social insects develop a plethora of other strategies to resist pathogens, including associations with symbiotic organisms (Chouvenc et al 2013;de Souza et al 2013). Corpse management is another essential adaptation to social life (Sun and Zhou 2013). The soldiers of many termite species produce potent defensive secretions that can have antifungal and antibacterial properties (Rosengaus et al 2000;Zhao et al 2004;Fuller 2007).…”
Section: Introductionmentioning
confidence: 99%